HUBUNGAN MOTIVASI DAN IKLIM KELAS TERHADAP HASIL BELAJAR FIQH DI MTSN 1 PESISIR SELATAN - Fithidayati Fithidayati (Universitas Islam Lamongan, 2022)
The purpose of this study is to determine the correlation of the variables X1, X2, and Y. By using the quantitative-correlational method, this study intends to determine the relationship between learning motivation, classroom climate, and learning achievement at MtsN 1 Pesisir Selatan. The research results show that; 1) there is a positive and substantial relationship between classroom climate and student learning outcomes, with a correlation coefficient of 48.4%; 2) there is a positive and significant relationship between the variables of learning motivation and student learning outcomes at MTsN 1 Pesisir Selatan by 0.3 percent while other variables influence 99.7 percent; 3) there is a positive and significant relationship between classroom climate variables and student learning outcomes at MTsN 1 Pesisir Selatan by 48.4 percent while other variables influence 51.6 percent. So it can be concluded that there is a positive and significant correlation between research variables